Kewenangan Pemerintah Menerapkan Sanksi terhadap Pelaku Distorsi Pasar Berdasar MaqÄsid al-SyarÄ«â€˜ah - Jabbar, Jabbar (Al-Manahij: Jurnal Kajian Hukum Islam, 2017)
The act of speculators distorting the market is quite unsettling. However, the Sharia texts show that this problem can be resolved using moral or akhlÄqÄ«. Then the question is whether the present government can overcome it by using qadÄ'Ä«e imposing sanctions for distortion. Since the nature of Sharia is the universal and eternal, this issue must be answered comprehensively and holistically. For that reason, the maqÄsid approach is operated with istislÄhiyyah method. This method is also referred to as al-ijtihÄd al-maqÄs}idÄ« which is done in two stages, namely takhrÄ«j al-manÄt and tahqÄ«q al-manÄt. It is believed that this method is quite relevant to answer two research questions. Firstly, how is maqÄs}id al-syar'ah in terms of market distortion? Secondly, does the government in syar'i be authorized to impose sanctions on the perpetrators of market distortion? The theory used to highlight this issue is the theory of al-wÄzi' put forward by Ibn â€˜Ä€syÅ«r. This conclu that the Sharia wants the circulation of goods in the market run smoothly. To that end, the government may impose sanctions if the distortion is done to the basic goods that can affect massively harm.